SETTLEMENT OF LAND DISPUTES DUE TO MULTIPLE CERTIFICATES IN THE NATIONAL DEFENSE AGENCY IN THE CITY OF BANDUNG BASED ON GOVERNMENT REGULATION NUMBER 24 OF 1997 CONCERNING LAND REGISTRATION Junto REGULATION OF THE MINISTER OF ATR/BPN NUMBER 11 OF 2016 REGARDING SETTLEMENT OF DEFENSE CASES - Saim Aksinuddin (SEAN Institute, 2023)
In fact, there are many kinds of land disputes, one of which is land disputes due to multiple certificates. A double certificate is a description of the juridical data and physical data on the same land object as the physical form in the form of a certificate. The reason for this double certificate arises because there is more than one description of the certificate with the same land parcel. The result of this problem causes the land parcels to experience overlapping administratively, either part of the land parcels or the whole land parcel. One of the social facts that occurred in the community due to double certificates was land in Cibakom Block, Kel. Sukarasa, Kec. Sukasari - Jalan Setrasari Kulon Kav-10 - Bandung City with verdict on case number 404 / Pdt.G / 2014 / PN.Bdg. The method used by the writer with descriptive analytical research specifications, the approach method is juridical normative, data collection techniques in literature and field documents, data analysis using a qualitative juridical approach, stages of research in literature and the field stage. Based on the series of research conducted by the author, it can be concluded that the cases that occurred in Blok Cibakom, Kel. Sukarasa, Kec. Sukasari - Jalan Setrasari Kulon Kav-10 - Bandung City is caused by negligence of the land officers (BPN Kota Bandung) in the lack of supervision and control over a policy, mistakes in the process of granting and registering land rights to other parties and being recognized by not having good faith by other parties, giving rise to illegal acts. Of course, an orderly land law should be able to be implemented properly and optimize land administration (registration and registration) and making land registration maps so that disputes due to multiple certificates do not occur again.